Mukolitic phytotherapy in respiratory diseases: studies continue - N. A. Shostak; A. I. Kryukov; N. L. Kunelskaya; A. B. Turovskiy (Медицинский совет, 2013)
Each year acute bronchitis affects about 5% of the world population. Majority of patients seek medical care when symptoms become severe, especially in the first week of the disease. So far, acute bronchitis is a reason for one million doctor visits per year.